2018
DOI: 10.1002/jso.25052
|View full text |Cite
|
Sign up to set email alerts
|

Improved survival for extremity soft tissue sarcoma treated in high‐volume facilities

Abstract: Treatment at high-volume hospitals was associated with fewer positive margins and increased overall survival at 2, 5, and 10 years. Continued efforts should focus on optimizing the balance between patient access to specialty care and experience of the treating center.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
37
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 57 publications
(39 citation statements)
references
References 38 publications
1
37
0
1
Order By: Relevance
“…A nationwide study by Blay et al 8 investigated 35 784 patients with sarcoma and found that surgery at a reference center was significantly associated with overall survival, findings that are supported by several other studies. When looking specifically at STS‐E, several studies utilizing the NCDB have demonstrated that facility surgical volume is associated with overall survival in the management of STS‐E 13,29 . Our study found that a higher hospital volume was indeed associated with improved survival in a multivariate analysis.…”
Section: Discussionsupporting
confidence: 53%
See 2 more Smart Citations
“…A nationwide study by Blay et al 8 investigated 35 784 patients with sarcoma and found that surgery at a reference center was significantly associated with overall survival, findings that are supported by several other studies. When looking specifically at STS‐E, several studies utilizing the NCDB have demonstrated that facility surgical volume is associated with overall survival in the management of STS‐E 13,29 . Our study found that a higher hospital volume was indeed associated with improved survival in a multivariate analysis.…”
Section: Discussionsupporting
confidence: 53%
“…Patients were further stratified by hospital procedural volume. An established threshold for hospital volume to be considered a “high‐volume” has not been established, though numerous studies report a similar range 13,29 . Therefore, procedural volume was determined by quartiles of both hospitals and patients to ascertain whether trends in differences across strata were consistent.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…With regard to the need for surgical expertise, there are recent data describing a higher rate of microscopic negative margins and a trend toward improved outcomes in patients treated at high‐volume centers with specialized sarcoma surgeons 7 . Furthermore, a recent study found that patients with extremity STS who underwent surgery at high‐volume hospitals had survival rates of 87% at 2 years, 73% at 5 years, and 58% at 10 years, whereas patients treated at low‐volume hospitals had survival rates of 84%, 65%, and 53%, respectively, for the same periods 11 . These findings support the axiom that surgical oncologists and orthopedic surgeons with experience in treating patients with STS are crucial and are more knowledgeable regarding the latest literature on oncologic surgical practices.…”
Section: Introductionmentioning
confidence: 99%
“… 16 In the setting of extremity sarcoma, a recent study using the National Cancer Database has shown that the ratio of amputation is only 8% and that of limb salvage is 92%. 17 In our case series, 4 patients suffered from sarcoma on a lower extremity, and limb salvage was achieved using the PAP flap.…”
Section: Discussionmentioning
confidence: 90%